2022
DOI: 10.14569/ijacsa.2022.0130750
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Deep Learning Model of Chili Disease Recognition with Small Dataset

Abstract: Due to its tasty and spicy fruit with nutritional qualities, chili is a demanding crop widely farmed around the world. Hence, it is essential to accurately determine the health status of chili for agricultural productivity. Recent years have seen impressive results in recognition fields due to deep learning approaches. However, deep learning models' networks need an abundant data to perform well and collecting enormous data for the networks is time-consuming and resource-intensive. A data augmentation method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The results showed that the trained models were effective, with an average accuracy performance of 97% ( Table 7 ). This research demonstrates the significance of data augmentation in improving the accuracy of DL models for assessing chilli health, which could increase agricultural output ( Aminuddin et al., 2022 ).…”
Section: Ai-based Automated Vegetables Disease Detection Classificationmentioning
confidence: 82%
“…The results showed that the trained models were effective, with an average accuracy performance of 97% ( Table 7 ). This research demonstrates the significance of data augmentation in improving the accuracy of DL models for assessing chilli health, which could increase agricultural output ( Aminuddin et al., 2022 ).…”
Section: Ai-based Automated Vegetables Disease Detection Classificationmentioning
confidence: 82%
“…In order to train neural networks, these edited photographs are added to the original collection of photos, increasing the data set size. Data augmentation is used to artificially expand the training data set [28].…”
Section: B Data Augmentationmentioning
confidence: 99%
“…Furthermore, a comparison is made between the proposed architecture and the Teacher/Student structure by considering the same training set. Deep learning-based CNN and Res Net-18 techniques are explained in Aminuddin et al (2022) to identify the affected Chilli leaf. The authors achieved an accuracy of 97% in terms of performance by considering the original and augmented datasets.…”
Section: Introductionmentioning
confidence: 99%